A rare case of ileocolic intussusception due to severe endometriosis. Issue 6 (19th June 2020) - Benigno, Luca; Lisarelli, Loriana; Sortino, Rosita; Neuweiler, Joerg; Steffen, Thomas
Abstract: Intestinal intussusception is a rare cause of intestinal obstruction; intestinal intussusception associated with endometriosis is very rare. The varied clinical presentations make the diagnosis demanding. In this article, we report the case of a young female patient with an intestinal obstruction due to intussusception. The successive histologic examination of the resected sample showed advanced endometriosis. This is a very rare entity with only a few similar cases reported in the literature.